A Supplement Based on Zn-Enriched Virgin Coconut Oil as an Antifungal agent for Vaginal Candidiasis Patients - . HERY WINARSI; . HERNAYANTI; AGUS PURWANTO (Microbiology Indonesia, 2008)
This research was conducted to investigate the amount of Candida albicans in vaginal secretion of Vaginal Candidiasis patients administered with Zn-enriched virgin coconut oil. Thirty respondents were selected based on several criteria as follows: the number of C. albicans colonies in the vaginal secretion was more than 105 cfu.ml-1, voluntary, healthy, willing to sign the informed consent and resided in Purwokerto. In Group A, 10 women were administered 2 tablespoons per day of Zn-enriched virgin coconut oil. In Group B, 10 women were administered 1 tablespoon per day of Zn-enriched virgin coconut oil; and in Group C, 10 women served as control group. Vaginal secretions were taken 3 times, before intervention (at baseline time), at 1 month and 2 months after intervention. Samples were taken by collecting vaginal secretions from the vaginal proximal region using a sterile cotton bud, which was then put into a tube containing sterile carrier media. The vaginal secretions were tested for the number of total C. albicans using Pour Plate Method. Two months after treatment, the number of colonies decreased from 4.4x106 to 2.5x106 cfu ml-1 (p=0.03) in Group A. There was no significant difference in the number of colonies between Group A and Group B, the number of C. albicans colonies was still above the normal range. Therefore, the recommended dosage of intervention with Zn-enriched virgin coconut oil is one tablespoon a day.